'Fake news' is the invention of a liar: How false information circulates within the hybrid news system. (July 2019) - Giglietto, Fabio; Iannelli, Laura; Valeriani, Augusto; Rossi, Luca
Alarmed by the oversimplifications related to the 'fake news' buzzword, researchers have started to unpack the concept, defining diverse types and forms of misleading news. Most of the existing works in the area consider crucial the intent of the content creator in order to differentiate among different types of problematic information. This article argues for a change of perspective that, by leveraging the conceptual framework of sociocybernetics, shifts from exclusive attention to creators of misleading information to a broader approach that focuses on propagators and, as a result, on the dynamics of the propagation processes. The analytical implications of this perspective are discussed at a micro level (criteria to judge the falsehood of news and to decide to spread it), at a meso level (four possible relations between individual judgements and decisions), and at a macro level (global circulation cascades). The authors apply this theoretical gaze to analyse 'fake news' stories that challenge existing models.